Anger’s Value in the Context of the Climate Movement - Wallaert, Sigrid (Passion: Journal of the European Philosophical Society for the Study of Emotions, 2025)
This article examines the role of eco-anger in climate activism, focusing on Greta Thunberg and other young activists. The article challenges two common arguments against anger as a communicative strategy: that it is inherently retributive and counterproductive, and that it reduces the uptake of the speaker’s message. Instead, the article proposes that anger involves a triad of desires: retributive desires, recognitive desires, and desires for future change. While recognizing the potential for testimonial injustice due to stereotypes surrounding young women expressing anger, the article argues that climate anger functions as an outlaw emotion with the potential to advance testimonial justice. The article argues that climate anger offers several advantages: it can motivate people to join the climate movement, it has revolutionary potential to challenge the status quo, and it is well-suited to building community among activists. Ultimately, the article concludes that anger can be a powerful tool in addressing the climate crisis, particularly when used strategically by activists like Greta Thunberg.